Morpho-Molecular charaterisation of intergeneric hybrids of Ascocentrum - Katare Renuka Shamrao (Department of Floriculture and Landscaping, College of Horticulture, 2019)
Morpho-molecular characterisation intergeneric hybrids of Ascocentrum was conducted at the Department of Floriculture and landscaping, College of Horticulture, Vellanikkara, during 2016-19 with the objective of characterising based on morphological and molecular analysis for commercial exploitation and compatibility assessment. Thirty varieties selected for the morphological characterisation. In quantitative characters Mok. Omayaiy Yellow showed highest plant height, internodal length and leaf breadth throughout the study period. Plant spread, leaf length and leaf area were highest in Kag. Youthong Beauty. Mok. Sayan × Ascda. Doung Porn was observed with highest shoot girth, shoot diameter and number of leaves. Ascda. Yip Sum Wah × V. JVB showed maximum number of roots, Mok. Khaw Phiak Suan × Ascda. Jiraprapa was observed with the highest root length and Mok. Chao Praya Sunset Yellow Spot with the highest root girth. Vasco. Aroonsri Beauty had the least values in all vegetative characters throughout the study period including plant height, spread, internodal length, shoot, leaf and root characters except the number of leaves which was the least in Mok. Khaw Phiak Suan × Ascda. Jiraprapa. Variety Vasco. Aroonsri Beauty also produced the maximum number of florets/spike and had the shortest internodal length. Cluster analysis with 14 different floral characters revealed 12 clusters at 75 per cent similarity. The highest inter-cluster distance was observed in cluster 6 and cluster 10. Cluster 6, which included Ascda. Sirichi Fragrance and Vasco Blue Bay White was found to have the lowest internodal length with the highest value LVII for number of florets per spike, also observed to have lower flower length and flower width. Cluster 10 was found to have the high mean values for spike length, flower length and flower width. In qualitative characters, based on growth habit, two types were found among the varieties viz., hanging and prostrate nature of growth. Leaf texture was found smooth and rigid with entire leaf margin. Leaf apex was acute in Vasco. Aroonsri Beauty and Ascda. Yip Sum Wah × V. JVB and was emarginated in rest of the hybrids. Wide variation was found among the flower colour, colour pattern, nature of petals and lip. Regarding post harvest traits, variety Mok. Omayaiy Yellow recorded highest fresh weight of spike and physiogical loss in weight. Whereas, variety Kag. Youthong Beauty took maximum days to start wilting of a floret. Mok. Chark Kuan Pink was observed to have longest vase life, spike longevity and highest water uptake. In visual evaluation the highest total mean score for the spike to use as a cut flower was observed in Mok. Omayaiy Yellow (54.6 out of 60), while the lowest was observed in Vasco. Blue Bay White. The highest mean score was obtained in Vasco. Pine River Pink (53.83) for plants for the indoor display. In pollen studies Ascda. Sirichi Fragrance and Mok. Sayan × Ascda. Doung Porn showed the highest pollen fertility and germination and these were selected as two male parents for further cross compatibility check. Vasco. Aroonsri Beauty and Kag. Youthong Beauty were found self-incompatible as well as cross incompatible with both the male patents and Vasco. Pine River Blue was found cross incompatible with Mok. Sayan. × Ascda. Doung Porn whereas, the rest of the varieties were found cross-compatible with both the male parents. LVIII Among the 21 SSR primers, ten generated polymorphic patterns. The number of amplicons detected varied from two to seven. The highest number of alleles was found in FJ539054, FJ539061 and JN375718. Primers DQ494847 (3) observed to have less number of amplicons. The PIC value ranged from 0.095 to 0.800.. One unique band was produced by JN375713 and FJ539050 primers in Kag. Samrong and Vasco. Aroonsri Beauty, respectively. The least Jaccard’s similarity value (0.05) was observed between Kag. Samrong and Ascda. Suksamran Sunlight, Ascda. Yip Sum Wah × V. Josephine Van Brero, Vasco. Aroonsri Beauty. The UPGMA clustering algorithm grouped the varieties into two main clusters. The variety Kag. Samrong clustered separately from all other members, whereas, other members were grouped in one cluster. At 50 per cent level of similarity, the hybrids grouped into 13 clusters. Out of 29 ISSR primers used, 20 showed amplification in all hybrids with polymorphic bands. ISSR primer (GACAC) 4 generated 11 amplicons, whereas, ISSR 901 generated 31 amplicons. ISSR primer (GACAC) 4 had lowest PIC value, and UBC810, the highest PIC value (0.926). The least Jaccard’s similarity value (0.03) was observed between Vasco. Blue Bay White and Mok. Khaw Phiak Suan × Ascda. Bicentennial Yellow Spot, which indicates that these hybrids are dissimilar to each other. The highest Jaccard’s similarity value was observed between Mok. Khaw Phiak Suan × Ascda. Bicentennial Yellow Spot and Mok. Chao Praya Sunset Yellow Spot. A UPGMA-based dendrogram separated the 20 hybrids of Ascocentrum orchids into two main clusters, each with 10 members. At 30 per cent level of similarity, all the 20 hybrids grouped into 14 different clusters. Six clusters were observed with two members each.